Applied_SSM[1]

# Applied Calculus, Enhanced Review Edition (with CengageNOW, Personal Tutor Printed Access Card)

This preview shows pages 1–4. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Section 0.1 1 Chapter 0 0.1 1. 2(4 + (-1))(2 Â·-4) = 2(3)(-8) = (6)(-8) = -48 3 . 20/(3*4)-1 = 20 12- 1 = 5 3- 1 = 2 3 5. 3 + ([3 + (-5)]) 3 - 2Â¿2 = 3 + (-2) 3 - 4 = 1-1 = -1 7. (2-5*(-1))/1-2*(-1) = 2 - 5 Â· (-1) 1- 2 Â· (-1) = 2+5 1 + 2 = 7 + 2 = 9 9. 2 Â· (-1) 2 / 2 = 2Â¿(-1) 2 2 = 2Â¿1 2 = 2 2 = 1 11. 2 Â· 4 2 + 1 = 2Â¿16 + 1 = 32 + 1 = 33 13 . 3^2+2^2+1 = 3 2 + 2 2 + 1 = 9 + 4 + 1 = 14 15. 3 - 2(-3) 2-6(4 - 1) 2 = 3 - 2Â¿9-6(3) 2 = 3 - 18 6 Ã— 9 = -15 54 = 5 18 17. 10*(1+1/10)^3 = 10 ï£­ ï£« ï£¸ ï£¶ 1 + 1 10 3 = 10(1.1) 3 = 10 Ã— 1.331 = 13.31 19. 3 ï£° ï£¯ ï£® ï£» ï£º ï£¹- 2 Â· 3 2-(4 - 1) 2 = 3 ï£° ï£¯ ï£® ï£» ï£º ï£¹-2 Ã— 9-3 2 = 3 ï£° ï£® ï£» ï£¹-18-9 = 3 Ã— 2 = 6 21. 3 ï£° ï£® ï£» ï£¹ 1 -ï£­ ï£« ï£¸ ï£¶-1 2 2 2 + 1 = 3 ï£° ï£® ï£» ï£¹ 1 -1 4 2 + 1 = 3 ï£° ï£® ï£» ï£¹ 3 4 2 = 3 ï£° ï£® ï£» ï£¹ 9 16 + 1 = 27 16 + 1 = 43 16 23. (1/2)^2-1/2^2 = ï£° ï£® ï£» ï£¹ 1 2 2- 1 2 2 = 1 4- 1 4 = 0 25. 3Â¿(2-5) = 3*(2-5) 27. 3 2-5 = 3/(2-5) Note 3/2-5 is wrong, since it corresponds to 3 2- 5. 29. 3-1 8+6 = (3-1)/(8+6) Note 3-1/8-6 is wrong, since it corresponds to 3 -1 8- 6. 31. 3 - 4+7 8 = 3-(4+7)/8 33. 2 3+x- xy 2 = 2/(3+x)-x*y^2 35. 3.1x 3- 4x-2- 60 x 2-1 = 3.1x^3-4x^(-2)-60/(x^2-1) 37. ï£° ï£® ï£» ï£¹ 2 3 5 = (2/3)/5 Note that we use only (round) parentheses in technology formulas, and not brackets. 39. 3 4-5 Â¿6 = 3^(4-5)*6 Note that the entire exponent is in parentheses. 41. 3 ï£° ï£® ï£» ï£¹ 1 + 4 100-3 = 3*(1+4/100)^(-3) Note that we use only (round) parentheses in technology formulas, and not brackets. Section 0.1 2 43. 3 2x-1 + 4 x- 1 = 3^(2*x-1)+4^x-1 Note that the entire exponent of 3 is in parentheses. 45. 2 2x 2-x+1 = 2^(2x^2-x+1) Note that the entire exponent is in parentheses. 47. 4e-2x 2-3e-2x = 4*e^(-2*x)/(2-3e^(-2*x)) or 4(*e^(-2*x))/(2-3e^(-2*x)) or (4*e^(-2*x))/(2-3e^(-2*x)) 49. 3 ï£° ï£® ï£» ï£¹ 1 -ï£­ ï£« ï£¸ ï£¶-1 2 2 2 + 1 = 3(1-(-1/2)^2)^2+1 Note that we use only (round) parentheses in technology formulas, and not brackets. Section 0.2 3 0.2 1. 3 3 = 27 3.-(2 Â· 3) 2 = -(2 2 Â· 3 2 ) = -(4 Â· 9) = -36 or-(2 Â· 3) 2 = -(6 2 ) = -36 5. ï£­ ï£« ï£¸ ï£¶-2 3 2 = (-2) 2 3 2 = 4 9 7. (-2)-3 = 1 (-2) 3 = 1-8 = - 1 8 9. ï£­ ï£« ï£¸ ï£¶ 1 4-2 = 1 (1/4) 2 = 1 1/4 2 = 1 1/16 = 16 11. 2 Â· 3 = 2 Â· 1 = 2 13. 2 3 2 2 = 2 3+2 = 2 5 = 32 or 2 3 2 2 = 8 Â· 4 = 32 15. 2 2 2-1 2 4 2-4 = 2 2-1+4-4 = 2 1 = 2 17. x 3 x 2 = x 3+2 = x 5 19.-x 2 x-3 y = -x 2-3 y = -x-1 y =- y x 21. x 3 x 4 = x 3-4 = x-1 = 1 x 23. x 2 y 2 x-1 y = x 2-(-1) y 2-1 = x 3 y 25. (xy-1 z 3 ) 2 x 2 yz 2 = x 2 (y-1 ) 2 (z 3 ) 2 x 2 yz 2 = x 2-2 y-2-1 z 6-2 = y-3 z 4 = z 4 y 3 27. ï£­ ï£¬ ï£« ï£¸ ï£· ï£¶ xy-2 z x-1 z 3 = (xy-2 z) 3 (x-1 z) 3 = x 3 y-6 z 3 x-3 z 3 = x 3-(-3) y-6 z 3-3 = x 6 y-6 = x 6 y 6 29....
View Full Document

{[ snackBarMessage ]}

### Page1 / 287

Applied_SSM[1] - Section 0.1 1 Chapter 0 0.1 1 2(4-1(2 Â-4...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online